Qurʾanic Ethics and Islamic Law - Abou El Fadl, Khaled (Journal of Islamic ethics, 2017)
The issue of Islamic law and morality has for the most part received scant attention in the modern age. This essay contributes to the exploration of possible ways of understanding the relationship of ethics to Shariʿah and Islamic law. The author’s objective in this essay is largely normative. While he makes every effort to root his arguments in the fabric of the Islamic tradition, this essay is not descriptive, but aspirational in the sense that he seeks to persuade readers of the desirability of specific understandings of the meaning of Shariʿah and the relationship between Islamic law and ethics. As a point of departure, the author accepts that the Qurʾan and the laws of God are binding, and that an Islamic theory has to be expressed within the framework of Islamic principles. He maintains that the dynamism and vitality of Islamic law must be preserved in the contemporary age, and that such a result is not possible without maintaining the liberty and innovative capacities of the individual.